Influence of gas-to-liquid (GTL) fuel in the combined blend of Jatropha biodiesel and diesel: an analysis of engine combustion–performance–emission parameters1. Issue 38 (30th April 2015) - Sajjad, H.; Masjuki, H. H.; Varman, M.; Kalam, M. A.; Arbab, M. I.; Imtenan, S.; Rashedul, H. K.
<x xml:space="preserve">Abstract</x> This study presents a comparative analysis of the blends of JBD (J20) and GTL fuel (G20) with diesel, including a ternary blend of JBD-GTL-diesel (DJG20), in the context of fuel properties, engine performance and emission characteristics.